Preparation and mechanical performance of fluorite tailings geopolymer precursor under alkaline heat activation - Hao Qiu; Hongtao Su; Hengyuan Liu; Zhijian Guo; Huifang Zhang; Juntao Ma; Xiao Wang (Scientific Reports)
Abstract As one of the bulk solid wastes in the Yellow River basin in China, fluorite tailings urgently need to be utilized as resources. In this paper, NaOH and Na2CO3 were used for alkali thermal activation of ground fluorite tailings under different temperature conditions, and the reactivity was analyzed by XRD, SEM and compressive strength after hydration, so as to evaluate the feasibility of fluorite tailings as geopolymer precursor. The results show that the fluorite tailings can exhibit certain reactivity under alkaline heat excitation, and significant amorphous glass phase can be detected. The better heat excitation temperature is 1000 °C, while there is not enough amorphous glass phase for hydration reaction at the lower or higher temperature. The compressive strength of the tailings harden paste can reach 7.2 MPa at 28d after excitation with 50%NaOH at 1000 °C, which is expected to be used as geopolymer precursor after excitation.